Penerapan Sikap Dan Perilaku Peduli Lingkungan Hidup Terhadap Siswa SMAN 1 Pangale Kabupaten Mamuju Tengah Sulawesi Barat - Aris, Aris; Mithen, Mithen; Ali, M Ichsan (UNM Environmental Journals, 2021)
This study aims to determine the attitudes and behavior of environmental care students of SMA Negeri 1 Pangale before and after participating in environemntal training. The type of research is descriptive quantitative and using the experimental approach. The research population was students of SMAN 1 Pangale, Central Mamuju Regency, West Sulawesi, with a total of 357 students. The research sample was taken using probability random sampling technique so that a total sample of 54 students was obtained which was divided into three levels, namely class X, class XI and class XII and 18 respondents could be selected for each level. The data analysis used is descriptive statistics and inferential statistics using paired sample t-test. The results showed that the environmental attitudes and behavior of students increased significantly before and after training based on descriptive analysis. The result also supported by the statistical analysis. Furthermore, the training on environmental care affects the attitudes and behavior of environmental care students at SMA Negeri 1 Pangale.